Digitale Strategien im Diabetesmanagement: Interventionspunkte für digitale Gesundheitsanwendungen auf den Patientenpfad von Typ-2 Diabetes - Annika Sophie Peters; Claudia Miersch; Sophie Brenner (IU Internationale Hochschule, 2025)
This study explores the strategic integration of digital health applications (DTx) within the therapeutic pathways for managing Type 2 Diabetes Mellitus (T2DM) in outpatient settings. We aim to pinpoint effective junctures for DTx intervention, employing a comprehensive four-step methodology which involves crafting a guideline-oriented patient care pathway and performing a structured literature review. Key functionalities and actionable intervention points for DTx within this care continuum were identified, providing essential insights for enhancing patient adherence and personalizing T2DM treatment. Our findings can aid future DTx design and the development of integrated care models that optimize therapeutic outcomes for T2DM patients.
Keywords: 330; Type 2 diabetes; digital health applications; DTx; digital therapies; treatment process; patient pathway